Hoaks Dalam Perspektif Komunikasi Islam - Priska Nur Safitri (Faculty of Ushuluddin and Dakwah, UIN K.H. Abdurrahman Wahid Pekalongan, Central Java, Indonesia, 2021)
The phenomenon of hoaxes confuses the public about the information received. However, irresponsible actors are used to gaining profits and instill hatred and slander in hoax news. This study focuses on hoax discourse through the study of Islamic communication. This research method uses qualitative to provide a holistic description of hoaxes through the study of Islamic communication. The results of this study are the application of Islamic communication ethics qaulan sadidan, qaulan baligha, qaulan ma'rufa, qaulan karima, qaulan layyina and qaulan maysura as amar ma'ruf nahi munkar based on the Qur'an Hadith. In addition to this, there are five steps of virtual Islamic communication ethics, namely being responsible, having empathy, checking authenticity, paying attention to wisdom and integrity. Built based on Islamic principles that include friendliness, peace, and safety of the people. Through Islamic communication, there will be a positive process in interactive communication, so that it can avoid hoax news both as creators, senders of news, and as consumers of hoax news consumers.